Australia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper reviews how Australia's economy has adapted to a flexible Australian Dollar. The paper provides a background on the float and the initial policy challenges. It discusses the main elements of the Future Fund proposal, and estimates how much Australia and other countries in the Asia-Pacific region would gain from greater financial integration. The results suggest that these welfare gains are large, giving an argument in favor of a progressive capital account liberalization across the region, once the needed supporting measures are in place.